Academic Senate Minutes 2012-09-17 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 9/13/12 approved. Information items – End of Year Reports from Senate, APC, EPC, Scholarship, AFS, PDS, Graduate Studies, and SDS. Resolution Regarding CSU Board of Trustees' Committee on Educational Policy September 2012 Agenda item 3, Upper Division General Education Degree Completion, Information [Amended] – amended and approved. CFA Report. Staff Representative Report. Opposition to Proposition 32: Political Contributions by Payroll Deduction. Contributions to Candidates. Initiative Statute. (The "Paycheck Protection" Initiative) 2012 – approved. Associated Students Report. Statewide Senator Reports. EPC Report. FSAC Report. SAC Report. Vice Chair Report.